Photocatalytic Oxidation of Gaseous Isopropanol Using Visible-Light Active Silver Vanadates/SBA-15 Composite - Ting-Chung Pan; Hung-Chang Chen; Guan-Ting Pan; Chao-Ming Huang (International Journal of Photoenergy)
An environmentally friendly visible-light-driven photocatalyst, silver vanadates/SBA-15, was prepared through an incipient wetness impregnation procedure with silver vanadates (SVO) synthesized under a hydrothermal condition without a high-temperature calcination. The addition of mesoporous SBA-15 improves the formation of nanocrystalline silver vanadates. In situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) confirms the presence of Brønsted and Lewis acids on the SVO/SBA-15 composites. The results of photoluminescence spectra indicated that the electron-hole recombination rate have been effectively inhibited when SVO was loaded with mesoporous SBA-15. All the composites loaded with various amount of SVO inherit the higher adsorption capacity and larger mineralization yield than those of P-25 (commercial TiO2) and pure SVO. The sample loaded with 51% of SVO (51SVO/SBA-15) with mixed phases of Ag4V2O7 and α-Ag3VO4 exhibits the best photocatalytic activity. A favorable crystalline phase combined with high intensities of Brønsted and Lewis acids is considered the main cause of the enhanced adsorption capacity and outstanding photoactivity of the SVO/SBA-15 composites.